Relationship between riparian vegetation and soil properties in a tributary of the river Tacotalpa, Tabasco, Mexico - Moreno-Jiménez, Victorio; Castillo-Acosta, Ofelia; Gama-Campillo, Lilly; Zavala-Cruz, Joel; Ortiz-Pérez, Mario Arturo (Instituto de Ecología, A.C., 2017)
The riparian vegetation has been strongly fragmented by human actions modifying its structure and ecosystem functions. We analyzed the relationship between soil properties and riparian vegetation variables from a tributary of the Tacotalpa River in Tabasco. Three zones were selected along the course: low, medium and high; eight 5 m × 50 m units were established on each sampling zone and all trees and shrubs with DAP ≥ 1cm were counted. The species were identified and information about the importance value index (IVI), species diversity (H’) and similarity index (IS) was generated. A soil sample was collected on each sampling unit on a depth of 0 cm - 30 cm, and texture properties, pH, organic matter (OM), total nitrogen (Nt), available phosphorus (P) and potassium (K) were analyzed. All variables were analyzed using SPSS and PAST statistical packages. On the three riparian vegetation areas, 1681 individuals, 38 families and 131 species were recorded; the Fabaceae, Euphorbiaceae and Moraceae families were the most representative. The diversity was similar in all three zones and the similarity ranged between 31.3% and 53.3%. The contents of Nt, MO and P were higher in soil of the upper area with most preservedvegetation and lower in low and middle areas with secondary vegetation. These edaphic variables were positively correlated with tree height (p < 0.01), being evident the beneficial effect of plant-soil interactions.